Pelaksanaan Hukuman Kebiri Kimia: Perspektif Hukum Pidana dan Hak Asasi Manusia - Nasrullah Nasrullah (SIGn Jurnal Hukum, 2022)
This study aims to understand and analyze how chemical castration aligns with Indonesia’s criminal law framework and human rights principles. This study uses normative legal research methods with the statute and conceptual approaches. The collected legal material is then qualitatively analyzed to describe the problem and answer the study objectives. The results show that chemical castration punishment, as regulated in Government Regulation in Lieu of Law Number 1 of 2016 and Government Regulation Number 70 of 2020, was established as a preventive measure against child sexual abuse. However, the relevance of this punishment must be viewed from two primary perspectives: criminal law and human rights. From the criminal law perspective, chemical castration serves the functions of retribution, rehabilitation, and deterrence, working synergistically to offer optimal protection for children from sexual violence. Meanwhile, from a human rights standpoint, there’s a critical need to ensure child protection without sidelining the human rights principles outlined in the UDHR, the 1945 Constitution, and Law Number 39 of 1999. Therefore, several recommendations regarding a comprehensive evaluation of the implementation of chemical castration punishment can be proposed to the Government. First, even though this policy aims to prevent child sexual abuse, an in-depth study from the criminal law viewpoint must be reinforced to ensure the effectiveness of the punishment’s three main functions: retribution, rehabilitation, and deterrence. Secondly, a review from the human rights perspective is equally essential. This policy must be ensured to align with the human rights principles embedded in the UDHR, the 1945 Constitution, and Law Number 39 of 1999. As a result, concrete steps such as amendments, law enforcement training, and public education are vital to optimize the chemical castration punishment in safeguarding children without neglecting human rights.